Measurement of Energy Efficiency Based on Economic Foundations - Massimo Filippini; Lester Hunt (ETH Zurich, CER-ETH - Center of Economic Research, 2015)
Energy efficiency policy is seen as a very important activity by almost all policy makers. In practical energy policy analysis, the typical indicator used as a proxy for energy efficiency is energy intensity. However, this simple indicator is not necessarily an accurate measure given changes in energy intensity are a function of changes in several factors as well as `true' energy efficiency; hence, it is difficult to make conclusions for energy policy based upon simple energy intensity measures. Related to this, some published academic papers over the last few years have attempted to use empirical methods to measure the efficient use of energy based on the economic theory of production. However, these studies do not generally provide a systematic discussion of the theoretical basis nor the possible parametric empirical approaches that are available for estimating the level of energy efficiency. The objective of this paper, therefore, is to sketch out and explain from an economic perspective the theoretical framework as well as the empirical methods for measuring the level of energy efficiency. Additionally, in the second part of the paper, some of the empirical studies that have attempted to measure the energy efficiency using such an economics approach are summarised and discussed.
Keywords: D; D2; Q; Q4; Q5; 330; economic foundations of energy efficiency; energy demand; stochastic frontier analysis